Modeling of large-scale disk perturbation eclipses of UX Ori stars with the puffed-up inner disks - Shulman Sergey; Grinin Vladimir (Open Astronomy, 2022)
Eclipses of UX Ori stars by compact gas–dust clouds and large-scale circumstellar disk perturbations are modeled. A flared disk and a disk with a puffing-up in the dust sublimation zone are considered. The disk puffing-up explains several observed features of eclipses. The linear polarization degree can remain unchanged during the eclipse. There might be no star reddening in the blue and ultraviolet spectral regions. Strong changes (up to 90°90\text{°}) in the positional angle of the linear polarization may happen when passing from one spectral band to another. An eclipse by a large-scale disk perturbation can be noticeably deeper than an eclipse by a compact gas–dust cloud. The polarization degree in such an eclipse can also be significantly higher. In addition, an eclipse by a large-scale perturbation of a star with a puffed-up disk explains the significant scatter of eclipse parameters at the same fading level. A significant change in the positional angle of the linear polarization may occur during a large-scale disk perturbation eclipse minimum and after it. We attempted parametric identification of long-lasted deep minima of UX Ori and WW Vul. The considered simple model can only partially explain the observed phenomena and need further development.